DIFFERENCES OF LIVER FUNCTION TESTS IN TYPE 2 DIABETES MELLITUS PATIENTS WITH AND WITHOUT CORONARY ARTERY DISEASE - Hendra Saputra; Burhanuddin Nasution; Santi Syafril (INDONESIAN JOURNAL OF CLINICAL PATHOLOGY AND MEDICAL LABORATORY, 2018)
One of the macroangiopathic complications of Diabetes Mellitus (DM) is Coronary Arterial Disease (CAD). Several studies showed that the liver was one of the organs involved in the pathological development of diabetes.The aim of this study was to find the differences of liver function in type 2 DM patients with CAD and without CAD. This was an analytical observational study with cross-sectional design. Forty-four type 2 DM patients with and without CAD at the Adam Malik Hospital Medan who came during June - August 2016 were studied for liver function (total bilirubin, direct bilirubin, AST and ALT). In this study, the average values of total bilirubin and direct bilirubin level in patients with CAD were found to be lower than without CAD. Statistically a significant difference revealed a total bilirubin (p < 0.001) and direct bilirubin (p = 0.001) in type 2 DM patients with and without CAD. There was a significant difference in liver function tests in DM type 2 patients with, and without coronary arterial disease, these data suggested that total billirubin and direct billirubin levels in type 2 DM patients with CAD were found lower than those without CAD.